THE DETERMINANTS OF FIRM PROFITABILITY IN INDONESIA - Muhani; Melati; Elwisam; Kumba Digdowiseiso; Nor Hayati Sa’at (RADJA PUBLIKA, 2024)
Profitability is a metric that evaluates the efficiency of a company's operations, specifically its capacity to generate or accumulate profits. Examining profitability offers a thorough perspective on the efficacy of company policies, which in turn affects the performance of management and, ultimately, the company's financial gains. Nevertheless, diverse studies yield contrasting outcomes when examining the factors influencing a company's capacity to generate profits. Researchers utilize qualitative research methods, particularly systematic literature reviews, to identify shared factors that influence profitability, thereby revealing patterns in these determinants. The researchers examined 9 out of the 49 identified journals and discovered that a company's assets or size, working capital, and expenses have a significant influence on its ability to generate profits